E-Business Development and the Factors Affecting of its Application in Hospitality Operations Sustainability - Ibrahim, Irwan; Ismail, Albert Feisal@Muhd Feisal; Amer, Afizan; Baharuddin, Farrah Nadia; Sarkun, Mif Rohim Noyo (International Journal of Supply Chain Management, 2020)
Abstract— Digital technology has become an essential catalyze for the tourism industry. Digital technology played a significant role in shifting the tourism sector into an impact driven industry. The process of putting the demand and supply planning and execution information into a collaborative mode through the internet helps the employees to communicate with customers, suppliers and other business functions swiftly and also helps to execute ordering, promising and processing and other services delivery more quickly at lesser cost. Now for an E- Business Supply Chain Management approach to function efficiently with inline key process, the performance objectives need to guide overall strategy and the design of the system in the following manner –Factors affecting the usage of E-Business Supply Chain Managemant in the tourism industry have been well-documented in developed countries, but further studies are needed to investigate the usage in the tourism industry among developing countries. This study aims to identify the level of E-Business Supply Chain Management usage as well as the benefits and barriers of its adoption in hospitality operation sustainability among local tourism agencies. The E-Business Measurement Evolution Model and the quantitative approached was applied for this study. Questionnaires were distributed to the respondents in the form of an online and self-administered questionnaire. Statistical Package for Social Science (SPSS) version 25.0 was used to analyze the data. The research findings revealed that tourism agencies in Malacca were still in the early stages of E-Business Supply Chain Management usage, with only (54%) of the travel agencies are online. The factor of saving time (M = 4.3492) was the key benefit in E-Business Supply Chain Management usage while the factor of hackers’ intervention (M = 3.8730) was revealed to be the most deterring factor that causes the tourism agencies reluctance to adopt E-Business Supply Chain Management practice.This study shows that government aims of E-business tourism have not been fully realized. The respondents still perceive the factors of internet fraud and security are a significant issue for E-business Supply Chain Management usage.Therefore, future research is recommended to provide more insights into the application of E-business Supply Chain Management application in tandem with the government aim of the hospitality operations sustainability Malaysian tourism industry.